"Vedno ko se peljem v avtu, mora biti radio" - Verovnik, Tina (Družboslovne razprave, 2022)
This paper focuses on understanding radio in the everyday life of young people: the role it plays in the context of their family life; how it is positioned relative to music; which novelties in the listening and selection of audio content do they practise. We rely on data from qualitative research performed in the project Media repertoires among youth, which included semi-structured group interviews with 67 young people aged 12–19 years. The radio is not listened to on their own initiative or individually, but with their parents; most often while they are driving around in the car. Their everyday life is most notably marked by music, which they primarily associate with listening on demand and at their own choice, through digital devices. These media choices are complemented by podcasts, especially among high school students.
Keywords: Digitalne komunikacije; družbeni mediji; komunikacijske prakse; Mediji; mladi; Mladina; mobilni mediji